Characterizing the ratio of nitrate to sulfate in ambient fine particles of urban Beijing during 2018–2019. (15th September 2020) - Li, Shangze; Zhang, Fang; Jin, Xiaoai; Sun, Yele; Wu, Hao; Xie, Conghui; Chen, Lu; Liu, Jieyao; Wu, Tong; Jiang, Sihui; Cribb, Maureen; Li, Zhanqing
Abstract: A variety of legislative actions for air quality improvement have been conducted in China since 2013, and the emission control measures have achieved remarkable reduction in severe haze frequency. The composition of the fine particles may change along with the improved air quality, and thus may induce distinct environmental and climate effects in future. In this study, a very recent long-term dataset (2018–2019) of non-refractory chemical composition measured by a quadrupole aerosol chemical speciation monitor (Q-ACSM) observed in urban Beijing is applied to investigate the changes in ratio of nitrate (NO3 − ) to sulfate (SO4 2− ) in PM2.5 (particulate matter with diameters of less than 2.5 μm). We show that the ratio of NO3 − to SO4 2− varies seasonally, with a maximum in winter (1.6 ± 1.2) and a minimum in summer (0.7 ± 1.0). Compared with results from earlier studies showing a continuous increase in the ratio of NO3 − to SO4 2− since 1999, a decline in the ratio is found during the period of 2018–2019. This is partially associated with an attenuated nitrate formation likely due to reduced nitrogen oxides emissions since 2016 in China. Our results suggest that the strict reduction control measures in place serve only to improve SO4 2− pollution in winter but not in summer when high SO4 2− levels are still observed. SO4 2− and NO3 − concentrations during study periods together comprise 37–53% of PM2.5, presenting significant role in dominating the levels of PM2.5 . In addition, we show that the ratio of NO3 − /SO4 2− in warm seasons generally increases with increasing relative humidity (RH) due to enhanced NO3 − hydrolysis formation, but with a maximum value of only ~1.0 that is pulled down by the high levels of sulfate in summer, while the dependence of the ratios on RH is more pronounced in cold seasons when multiple factors (regional transportation, planetary boundary layer, PBL and sources of sulfate, etc.) can impact nitrate levels. We finally characterize two typical processes that lead to the rapid accumulation of nitrate in the atmosphere over urban Beijing: the regional transportation and PBL variations, which is found driving heavy haze in cold seasons, and the hydrolysis formation and partitioning of NO3 − that tends to impact the diurnal patterns of nitrate in warm seasons. Highlights: The ratio of NO3 − to SO4 2− in 2018–2019 declined. A continuous increase in the ratio of NO3 − to SO4 2− of 1999–2018 is presented. The reduction measures in place serve only to improve SO4 2− pollution in winter. High SO4 2− levels are still observed in summer.